2007
DOI: 10.1534/genetics.106.066613
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure ofDrosophila ananassaePopulations From Asia, Australia and Samoa

Abstract: Information about genetic structure and historical demography of natural populations is central to understanding how natural selection changes genomes. Drosophila ananassae is a widespread species occurring in geographically isolated or partially isolated populations and provides a unique opportunity to investigate population structure and molecular variation. We assayed microsatellite repeat-length variation among 13 populations of D. ananassae to assess the level of structure among the populations and to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
50
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 46 publications
13
50
2
Order By: Relevance
“…Similar studies (Vogl et al, 2003;Das et al, 2004;Schug et al, 2007) done earlier at molecular level in D. ananassae have arrived on the similar conclusion. These studies have shown that F ST values of the order of 0.1 (much lower than our F ST estimates) could be applied to Indian populations.…”
Section: Gene Flowsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar studies (Vogl et al, 2003;Das et al, 2004;Schug et al, 2007) done earlier at molecular level in D. ananassae have arrived on the similar conclusion. These studies have shown that F ST values of the order of 0.1 (much lower than our F ST estimates) could be applied to Indian populations.…”
Section: Gene Flowsupporting
confidence: 84%
“…ananassae displays high population sub-structure across the whole distribution range (Stephan, 1989;Stephan & Langely, 1989;Stephan & Mitchell, 1992;Stephan et al, 1998;Das, 2005;Schug et al, 2007). It exhibits more population structure than both D. melanogaster and D. simulans (Vogl et al, 2003;Das, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mean D 0 estimates, we use for each population the percentage of locus pairs that had significant (Po0.05) D 0 values. As 5% of pair-wise LD are expected by chance to be significant, higher percentages indicate more LD than would be expected (Schug et al, 2007).…”
Section: Methodsmentioning
confidence: 90%
“…Furthermore, comb size in Noumea is significantly greater than at Cape Tribulation , indeed indicating the probable recent evolution of alleles conferring large ornament size in New Caledonia, which may be destabilizing trait-specific networks (Clarke & McKenzie 1987;Sangster et al 2004). This model assumes that New Caledonian D. bipectinata is derived from mainland Australia (or Southeast Asia), which is reasonable (Kopp & Barmina 2005;Schug et al 2007). …”
Section: Discussionmentioning
confidence: 96%